Respostas

2014-08-31T10:24:43-03:00
A) f(x)=3
-2x+3=3
-x=3-3/2
x=-0/2

b) f(x)=1
-2x +3=1
-x=(1-3)/2
x=1

c) f(x)=-7
-2x+3=-7
-x=(-7-3)/3
x=10/3

d) f(x)=0
-2x+3=0
x=3/2
1 1 1
  • Usuário do Brainly
2014-08-31T11:14:02-03:00
Olá, Thayná !

f(x)=-2x+3

a) f(x)=3

Se f(x)=3, significa que, -2x+3=3~\Rightarrow~~-2x=0~~\boxed{x=0}.


b) f(x)=1

Sendo f(x)=1, temos -2x+3=1, ou seja, -2x=-2 e obtemos \boxed{x=1}


c) f(x)=-7

Analogamente, -2x+3=-7~\Rightarrow~2x=10~\Rightarrow~\boxed{x=5};


d) f(x)=0

Temos -2x+3=0~~\Rightarrow~~2x=3~~\Rightarrow~~\boxed{x=\dfrac{3}{2}}.

Espero ter ajudado, até mais ^^